2018
DOI: 10.12738/estp.2018.5.150
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mooc-based Flipped Classroom in the Teaching Reform of Piano Course

Abstract: Along with the deepening and reform of piano teaching, piano teaching resources have been optimized and integrated. The application of Internet technology provides a new opportunity for piano teaching mode and talents training in colleges and universities. Mooc teaching breaks the traditional teaching mode of group class and collective class, and flipped classroom can expand the piano subject practice. Based on the network technology, this study explores the application of the teaching mode of Mooc-based flipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…It has been previously reported that the use of MOOCs brings new opportunities for the development of music education (Shu, 2018). Whereas in traditional teaching teachers play an active role and students are passive, the use of MOOCs requires activation from a student (Liu, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the use of MOOCs brings new opportunities for the development of music education (Shu, 2018). Whereas in traditional teaching teachers play an active role and students are passive, the use of MOOCs requires activation from a student (Liu, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Hemos afirmado que el uso de los MOOC abre nuevas oportunidades para el desarrollo de la educación musical (Shu, 2018). Mientras que en la enseñanza tradicional, los docentes desempeñan un papel activo y los estudiantes uno pasivo, el uso de los MOOC requiere la activación del estudiante (Liu, 2020).…”
Section: Discussionunclassified
“…MOOC platform is easier for students to attain learning resources and apply their abilities to practical application ( Shu, 2018 ). Implementation of flipped classroom model is believed to enable teachers to better engage students and facilitate them in active learning, resulting in better learning outcomes ( Freeman et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…MOOC, in particular, is an innovative teaching and learning phenomenon rapidly penetrating higher education and has received wide attention from educators ( Ahmed et al, 2022 ). It breaks the barrier between classroom teaching and practice teaching, realizing the comprehensive integration of different teaching links ( Shu, 2018 ). In addition, it has gradually attacked traditional classroom teaching with its advantages of high-quality resources, rich teaching formats, convenient learning methods, and robust interactivity.…”
Section: Introductionmentioning
confidence: 99%